UPAYA-UPAYA KONKRIT MENDISIPLINKAN DOSEN MELAKSANAKAN PERKULIAHAN - Reresi, Marsianus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2014)
This article wants to analyze concrete steps by which to discipline university teachers in performing their lessons. The central question which we will try to answer in this piece of writing is: “What efforts should be performed by the respective responsible in disciplining the teachers to execute their lessons?” Definite efforts to discipline teachers in executing their lessons is part of the important task of the basic governance of schools at university level in guiding and enhancing awareness and comprehensiveness of teachers‟ discipline in performing their lessons.